On path independent stochastic choice - David S. Ahn; Federico Echenique; Kota Saito (Theoretical Economics, 2018)
We investigate stochastic choice when only the average and not the entire distribution of choices is observable, focusing attention on the popular Luce model. Choice is pathindependent if it is recursive,in the sense that choosing from a menu can be broken up into choosing from smaller submenus.While an important property, path independence is known to be incompatible with continuous choice. The main result of our paper is that a natural modification of path independence, which we call partial path independence, is not only compatible with continuity, but ends up characterizing the ubiquitous Luce (or logit) rule.
Keywords: D01; D11; 330; Luce model; stochastic choice; logit model; path independence